A influência do comportamento de liderança nas reações individuais à mudança: estudo sobre a criação e constituição do IFMG. - Renata Veloso Santos Policarpo (2016)
This research aims to analyze the influence of leader behavior with the intention of servers to resist or cooperate with the process of creation and structuring of the management model of the "Instituto Federal de Minas Gerais" - IFMG. For this, it was used the theoretical concepts developed by Bass (1985) and Bass and Avolio (1990) on the model of transactional and transformational leadership and also followed the guidance of the Cooperation Model and Resistance to Change developed by Marques, Chaves and Dias ( 2005) and revalidated by and Borges and Marques (2011) and Marques (2012). From the understanding of individual reactions to change and the study of the theory of transactional and transformational leadership suggested examining the inter-relationship between these constructs in changing searched. The Instituto Federal de Educação, Ciência e Tecnologia de Minas Gerais originated in 2008, target of a restructuring in Professional Education Network and technology in the country, with the integration of three former Autarchys CEFET Bambuí, CEFET Ouro Preto and Escola Agrotécnica Federal de São João Evangelista and also the "Unidades Descentralizadas de Ensino" (UNED's) Congonhas and Formiga, and has now become a multicampi institution in the State of Minas Gerais. And in this scenario, in order to achieve the proposed objectives, it was developed then a study of quantitative and qualitative case, descriptive and explanatory. Thus, a quantitative and qualitative research through the use of questionnaires and interviews was conducted. Quantitative data were analyzed using multiple regression and demographic data through descriptive statistics. As to the qualitative analysis, it was performed through content analysis. A sample of 57 respondents was obtained, and all experiencers were of the creation and constitution of IFMG management model. In the qualitative analysis, it was interviewed 15 individuals, stratified by campi of origin, using a semi-structured script. The research also involved the use of secondary data, such as: document analysis and literature about the changes implemented in the network of educational, professional and technological. Data analysis has shown that transformational leadership style does not positively influence cooperation and acceptance of organizational change as well as the transactional leadership styles and "laissez-faire" does not negatively influence the cooperation and acceptance of changing. What has been confirmed is that the behavior of the leadership whose dimensions are the extra effort, effectiveness and satisfaction, could positively influence the cooperation and individual acceptance of changing. These results show that the behavior and leadership performance serves as a measure of success for the group and is based on the level of motivation of the subordinates, in the acting leader along with other organizational spheres and, finally, the level of satisfaction of subordinates before the leader as broached on the theory presented by Avolio and Bass (2004). Until now, just a few references found in the national literature had mentioned the importance of the correlation of such aspect, so this may be an important contribution of this study to the field, and a significant opportunity for future researchs in the intersection between leadership and reaction of change in organizations. Furthermore, the research contributions may also offer subsidies for training programs and structure of future leaders to act in changeover projects.